Inherited Developmental and Epileptic Encephalopathies - Emanuele Bartolini (MDPI AG, 2021)
Epileptic encephalopathies often have a genetic etiology. The epileptic activity itself exerts a direct detrimental effect on neurodevelopment, which may add to the cognitive impairment induced by the underlying mutation ("developmental and epileptic encephalopathy"). The focus of this review is on inherited syndromes. The phenotypes of genetic disorders affecting ion channels, metabolic signalling, membrane trafficking and exocytosis, cell adhesion, cell growth and proliferation are discussed. Red flags suggesting family of genes or even specific genes are highlighted. The knowledge of the phenotypical spectrum can indeed prompt the clinician to suspect specific etiologies, expediting the diagnosis.